Nonlinear wave propagation in a hexagonally packed granular channel under rotational dynamics. (15th December 2015) - Yang, Jinkyu; Sutton, Michael
Abstract: In the present work, we numerically and experimentally investigate the propagation of nonlinear waves in a hexagonally packed granular channel. Specifically, we assemble a simple 1-2-1 granular chain, which triggers not only normal but also tangential interactions of particles up on a striker impact. We experimentally measure the transmission of nonlinear waves propagating along the channel direction using an embedded piezoelectric sensor particle. For numerical simulations, we introduce a discrete element model that accounts for both elastic and damping effects in axial and rotational directions. As a result, we find that the wave propagation in this 1-2-1 hexagonal architecture is governed strongly by the rotational dynamics of particles. We also verify that the effect of rotational damping is crucial for the accurate description of the particle's dynamics. The findings in this study hints the significance of particles' rotational dynamics when stress waves propagate along hexagonally packed particle channels even in highly ordered 2D/3D granular architectures.